Analysis of fractional boundary value problem with non local flux multi-point conditions on a Caputo fractional differential equation - SUBRAMANIAN, Muthaiah; KUMAR , A Ramamurthy Vidhya; GOPAL, Thangaraj Nandha (Studia Universitatis Babeș-Bolyai Mathematica, 2019)
A brief analysis of boundary value problem of Caputo fractional differential equation with nonlocal flux multi-point boundary conditions has been done. The investigation depends on the Banach fixed point theorem, Krasnoselskii- Schaefer fixed point theorem due to Burton and Kirk, fixed point theorem due to O’Regan. Relevant examples illustrating the main results are also constructed. Mathematics Subject Classification (2010): 34A08, 34A12, 34B10.